Analisis Penyebab Rendahnya Minat Belajar Siswa Dalam Pembelajaran Matematika Di Sekolah Dasar - Isthifara Isthifara; Kadek Arya; Karin Karin; Dini Dini; Ni Made Riastini (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The low interest of students in learning mathematics is a finding or problem that must be done. This study aims to determine what are the factors that cause low interest in learning mathematics. This research activity was carried out by interview, observation and documentation. This research was conducted using a qualitative method with a case study analysis research type, the subjects in this study were class teachers,students and parents of students. The key instrument of this study is the researcher himself, but in its implementation the researcher used tools such as a voice recorder, camera, interview guidelines and observation guidelines. The technique used is snowball sampling. Based on the research that has been done, several factors were found that influence students' interest in learning mathematics, that the factors causing low interest in learning mathematics are as follows: internal student factors can be shown by 1) student attitudes 2) Student assumptions / assume that learning mathematics is scary, difficult learning. Students do not know multiplication besides that the formulas in learning mathematics are many formulas and as a result, students' mathematics scores are diverse (low). Factors causing students' lack of interest in learning also come from external factors, namely students' environmental factors, such as lack of attention from parents and inadequate learning facilities.